2013
DOI: 10.1186/1476-4598-12-66
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling regulates hypoxia induced epithelial to mesenchymal transition and invasion in pancreatic cancer cells via a ligand-independent manner

Abstract: BackgroundHypoxia plays a vital role in cancer epithelial to mesenchymal transition (EMT) and invasion. However, it is not quite clear how hypoxia may contribute to these events. Here we investigate the role of Hedgehog (Hh) signaling in hypoxia induced pancreatic cancer EMT and invasion.MethodsPancreatic cancer cells were cultured under controlled hypoxia conditions (3% O2) or normoxic conditions. HIF-1α siRNA, cyclopamine (a SMO antagonist) and GLI1 siRNA were used to inhibit HIF-1α transcription or Hh signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
130
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 45 publications
7
130
0
Order By: Relevance
“…Sun et al (12) recently indicated that curcumin could reverse pancreatic cancer progression by inhibiting the Hh signaling pathway. The Hh signaling pathway, which is considered to play an important role in tumorigenesis, is normally quiescent in adult pancreas and has been shown to be very active in pancreatic cancer (5). Our previous study showed that hypoxia-induced invasion and EMT process is intimate related with the Hh signaling pathway (5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sun et al (12) recently indicated that curcumin could reverse pancreatic cancer progression by inhibiting the Hh signaling pathway. The Hh signaling pathway, which is considered to play an important role in tumorigenesis, is normally quiescent in adult pancreas and has been shown to be very active in pancreatic cancer (5). Our previous study showed that hypoxia-induced invasion and EMT process is intimate related with the Hh signaling pathway (5).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor hypoxia is strongly associated with enhanced tumor invasiveness, angiogenesis and distant metastasis (4). Hypoxia-inducible factor-1 (HIF-1), which belongs to the basic helix-loop-helix-periodic acidSchiff domain transcription factor family, is a key mediator of the cellular response to hypoxia and is overexpressed in a wide variety of solid tumors, including pancreatic cancer (5). Our previous study identified that the Hedgehog (Hh) signaling modulated hypoxia induced pancreatic cancer epithelial to mesenchymal transition (EMT) and invasion (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation of increased migration in the device with cells maintained under 1% oxygen is consistent with an extensive literature, suggesting that hypoxia generates a more aggressive phenotype 53,54 and was found in traditional transwell chamber assays for the PANC-1 cell line. [55][56][57] It should be noted that in these earlier studies, cells were trypsinized and resuspended in low-serum medium and a chemoattractant was used in each invasion assay. [55][56][57] In this communication, trypsinization, which may affect viability and invasiveness, was not necessary for the invasion assay nor was a chemoattractant (other than oxygen) added to induce migration.…”
Section: F Cell Experiments and Growth Rate Comparisonmentioning
confidence: 99%
“…[55][56][57] It should be noted that in these earlier studies, cells were trypsinized and resuspended in low-serum medium and a chemoattractant was used in each invasion assay. [55][56][57] In this communication, trypsinization, which may affect viability and invasiveness, was not necessary for the invasion assay nor was a chemoattractant (other than oxygen) added to induce migration.…”
Section: F Cell Experiments and Growth Rate Comparisonmentioning
confidence: 99%